NEW UZBEKISTAN AND HIGHER EDUCATION: REFORMS, OPPORTUNITIES, AND PROSPECTS - Nurxonov Muhammadi Nabi o‘g‘li (Western European Studies, 2025)
This article examines the ongoing reforms in higher education in New Uzbekistan, highlighting the modernization of university structures, expansion of academic programs, and increased opportunities for students and faculty. The study explores the development of new faculties, departments, and specializations, the enhancement of teaching and research capacities, and the implementation of modern pedagogical and digital technologies. It also considers the prospects for international collaboration, academic mobility, and the overall impact of these reforms on the quality of education and socio-economic development in the country
Keywords: New Uzbekistan; higher education; educational reforms